Vulnerability Assessment of Coastal Fisher Households in Tamil Nadu, India: A Climate Change Perspective - Johnson, B , Shyam S. Salim , V. Kripa , P. U. Zachariah , P. S. Swathilekshmi and A. K. Abdul Nazar, (Indian Journal of Extension Education, 2016)
Climate change is predicted to have a wide range of impacts on fisheries and those who depend on them. Coastalvulnerability describes the exposure of the natural system and of coastal livelihoods towards exigencies. The climatechange has multidimensional impacts on environment, fishery, social, economic and development drivers. The perceptionlevel of the primary stakeholders- leads to their proactive participation in disaster management plans. The present paperassessed the vulnerability of 400 fisher households in Ramanathapuram district of Tamil Nadu, India using PARSmethodology - Parameter, Attribute, Resilient Indicator and Score. The methodology provides prioritization and rankingof the different impacts as perceived by the fishers on the different environment, fishery and socio economic parameters.The vulnerability indices were worked out for the fisher households. The fishers' perception revealed that fishery wasmost impacted followed by economic and environmental impacts. The study indicated that long term effects of climatechange aren't realized/perceived impacted much among the fisher households. The fishers were more prone to loss in,fishing days due to erratic monsoon. The paper suggested the immediate need to improve the primary stakeholdersawareness by involving them in disaster preparedness, management and mitigation planning and implementation process.